2015
DOI: 10.1016/j.jneumeth.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Long-term imaging of circadian locomotor rhythms of a freely crawling C. elegans population

Abstract: Background Locomotor activity is used extensively as a behavioral output to study the underpinnings of circadian rhythms. Recent studies have required a populational approach for the study of circadian rhythmicity in Caenorhabditis elegans locomotion. New method We describe an imaging system for long-term automated recording and analysis of locomotion data of multiple free-crawling C. elegans animals on the surface of an agar plate. We devised image analysis tools for measuring specific features related to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 39 publications
(55 reference statements)
0
22
0
Order By: Relevance
“…The bacteria formed a circle of 0.6 cm diameter in the middle of the plate. Movies were taken on a custom-built imaging system and worm tracking software (Volumetry, version 8.a) [111] using a USB 2.0 monochrome machine vision cameras (Point Grey Research, CMLN-13SM-CS) equipped with a 12.5 mm focal length C-mount lenses (Fujinon, HF12.5HA-1B). All imaging was performed under dark field illumination using low angle red-light LED rings as a light source, such that worms appeared as white objects against a dark background.…”
Section: Methodsmentioning
confidence: 99%
“…The bacteria formed a circle of 0.6 cm diameter in the middle of the plate. Movies were taken on a custom-built imaging system and worm tracking software (Volumetry, version 8.a) [111] using a USB 2.0 monochrome machine vision cameras (Point Grey Research, CMLN-13SM-CS) equipped with a 12.5 mm focal length C-mount lenses (Fujinon, HF12.5HA-1B). All imaging was performed under dark field illumination using low angle red-light LED rings as a light source, such that worms appeared as white objects against a dark background.…”
Section: Methodsmentioning
confidence: 99%
“…Similar results regarding tax-2 involvement were described by van der Linden et al (19), who reported that a mutation in TAX-2 abolished the circadian expression of different transcripts entrained under either LD or WC conditions, indicating that TAX-2 is required for the transduction of both zeitgebers. In addition, tax-2 also was recently shown to be required for the transduction of thermal cues to the C. elegans circadian clock in locomotor activity rhythms (12). However, no evident role for lite-1 in light-entrained transcripts has been found previously (19), and to our knowledge there are no studies linking gur-3 to the input pathways of the clock.…”
Section: Discussionmentioning
confidence: 87%
“…Therefore our luciferase-based approach, which allows the recording of singlenematode molecular rhythms in real time and in intact animals, is a more sensitive and reliable method for revealing transcriptional rhythms. This fact is particularly relevant when working with C. elegans, in which circadian outputs do not appear to be particularly robust and there is a marked variability among nematodes (10)(11)(12)52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 8 flies were individually placed in DAMS activity tubes, and their movement was recorded and video captured. Analysis of activity was performed using custom-written image analysis software within the Volumetry application environment as previously described (Winbush et al, 2015). Briefly, movies were background subtracted leaving only individual flies; an intensity threshold was then applied to adequately outline each fly.…”
Section: Methodsmentioning
confidence: 99%